PREHOSPITAL EMERGENCY CARE AND PROFESSIONAL BURNOUT: NURSES IN FOCUS: Prehospital Emergency Care and Professional Burnout - Araujo-Filho, Irami; Medeiros da Silva, Lázaro Deogenes; Meneses do Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2023)
Burnout syndrome among nurses working in mobile emergency services is a relevant issue, as it influences the well-being of health professionals and the quality of care provided. Understanding the factors related to Burnout in this population is crucial for developing effective prevention and intervention strategies. This review aimed to critically analyze the Burnout syndrome in nurses working in mobile emergency services. After carefully selecting studies in relevant databases, a high workload, exposure to critical incidents, lack of organizational support, and inadequate coping mechanisms were identified. These factors promote emotional exhaustion, depersonalization, and a reduction in personal fulfillment, central components of the Burnout Syndrome. The need for interventions to face the challenges and risk factors involved in the illness process is highlighted. The importance of organizational support, workload management, and implementation of coping strategies to mitigate Burnout and improve the general well-being of nurses in this environment was emphasized. Additional research is needed to develop evidence-based interventions that effectively prevent and alleviate Burnout in this population.